Innovative Nanocomposite Resins in Implants, Pain Management, and Post-Operative Care: Bridging Durability with Antimicrobial Technology by Meta-Analysis - Amna Mehwish Ikram; Waqas Memon; Muhammad Haseeb Rana; Farah Tasleem; Erum Rehman; Kashaf Ali (Pakistan Journal of Medicine and Dentistry, 2025)
Background: Dental resins are widely available in clinical practice, but they are susceptible to microbial colonization. Nanotechnology is used as a potential solution to simultaneously enhance mechanical stability and antimicrobial efficacy for pain management. This study assessed the antimicrobial effectiveness of nanocomposite dental resins in pain management using a systematic review and meta-analysis of in vitro studies.